Fathers parenting behavior and psychological well-being of adolescents in a collectivist society - Yahya, Amira Najiha; Sumari, Melati; Zulkefly, Nor Sheereen; Baharudin, Rozumah; Mohd Kadri, Nursyuhaidah (City of University Hong Kong Press, 2023)
The present study examines the relationship between perceptions of a father's parenting behavior (i.e., warmth, monitoring, harsh discipline, and indigenous) and psychological well-being (self-esteem and psychological health) among 707 Malaysian adolescents aged between 13 and 16 years. The study also tests whether the relationships are mediated by self-esteem. Finally, the study also examines whether these relationships varied by adolescents' sex and age group. Cross-sectional data were collected from a battery of questionnaires and analyzed using descriptive statistics, correlation analysis, and structural equation modelling multi group test was employed to note the difference between groups. Bootstrapping analysis was performed to test the mediation effect. Father's warmth and indigenous parenting were indirectly related to the adolescents' psychological health via self-esteem, while harsh discipline was directly yet negatively related to the adolescents' psychological health — no significant contribution of fathers’ monitoring behavior toward adolescents' psychological well-being. The structural study model was stable across younger and older adolescents but varied across sex. Findings from the present study build on existing literature by providing a better framework for understanding adolescents' psychological well-being. Educators, practitioners, and those working with or for adolescents may find information from the present valuable study for designing various prevention and intervention programs related to adolescents' psychological well-being.